Analisa Hasil Pencucian Bijih Timah Pada Harz Jig Dalam Menurunkan Kadar Timah (Sn) Pada Tailing di PT Timah (Persero) Tbk. Unit Kundur, Kepulauan Riau - Debi Yulian Adinata; Yulan Indah Permatasari (Jurusan Teknik Pertambangan, Fakultas Teknik, Universitas Bangka Belitung, 2016)
Tin ore washery Sn) is less than the maximum will affect the waste of precious minerals togethertailings resulting in increased levels of tin in the tailings. This is certainly a serious problem for thecompany, the impact of the loss will be visible both from time, labour, etc. And certainly not inaccordance with the target company based on Standard Operating Procedure (SOP). To determinethe levels of Tin (Sn) is still contained in the tailings, the tailings assessments conducted usingmicroscopic analysis.Tailings samples studied came from washery tailings back to the concentratefrom the mining and leaching earlier in Dredger (KK) and Ship Suction (KIP) is brought to the Tin OreProcessing Center (PPBT). Cassetrite or primary mineral Tin (Sn) dominant in the size fraction (+ 50# -20 #) with a percentage weight of 1.176%, and the largest number of samples contained in thetailings coming from Ships Suction (KIP) 4 that is equal to 2.61%. Cassetrite for the weightpercentage of all samples of the tailings is 3:09% and obtained his Levels is 2:44% Sn. The resultsobtained are presented in tables and graphs. Based on microscopic analysis and calculation of Sn inthe whole sample of tailings Dredger (KK) and Ship Suction (KIP), the results turned out to be not inaccordance with the Standard Operating Procedure (SOP) of the company is 1%.